Association of feline morbillivirus infection with defined pathological changes in cat kidney tissues - Kripitch Sutummaporn (2020)
© 2018 The Authors Feline morbillivirus (FeMV) is an emerging member of morbillivirus discovered in 2012. Although association of FeMV infection with kidney diseases in cats has been suggested, the pathogenicity of the virus has not been clear to date. To study the association between FeMV infection and pathological changes in kidney tissues of infected cats, we performed immunohistochemistry and immunofluorescent assays to detect FeMV antigens and analyzed the effect of FeMV infection on the pathological changes in the kidney tissues. In 38 kidney tissue samples from cats, some tissue injury scores were significantly higher when the FeMV antigens were detected, especially those for the tubular tissues in which the FeMV antigens were mostly localized. Pathological changes associated with the FeMV antigens included the ones typically found in chronic kidney diseases, such as interstitial cell infiltration, glomerulosclerosis, tubular atrophy and fibrosis. We also detected some feline IgG localizations in glomerular tissues, though co-localization or significant association with the FeMV antigens were not found. Our study confirms the association of FeMV infection with some kidney tissue injuries and provides additional information about roles of FeMV infection in chronic kidney diseases.